Study Implementation Constraints of Agribusinees Dragon Fruit in Lubuk Lancang Village Suak Tapeh District Banyuasin Regency. - Ramadhan, Muhammad; Abubakar, Rafeah; Iskandar, Sutarmo (Universitas Muhammadiyah Palembang, 2015)
Purposes of this study were to determine the implementation of Agribusiness dragon fruit in Lubuk Lancang District of Suak Tapeh Banyuasin. To determine the constraints Agribusiness dragon fruit in Lubuk Lancang District of Suak Tapeh Banyuasin.Then to determine the level of revenue and profits dragon fruit in Lubuk Lancang District of Suak Tapeh Banyuasin.This research was conducted in the village of Lubuk Lancang District of Suak Tapeh Banyuasin from March until May 2015. The method of the research was a survey, for sampling methods was done by purposive sampling. Data collection methods used in this study were the observation and interviews directly to the respondents who have been determined by using the tools in the form of a questionnaire that had been prepared in advance. Data processing was done by tabulation and then analyzed descriptively with qualitative approach and descriptive analysis with mathematical approach .The results of the research showed that, Study Implementation Constraints of Agribusinees Dragon fruit includes: Procurement production facilities subsystem, farming subsystem, marketing subsystem.The way to sell dragon fruit that was done by the farmers is by the consumer come directly to localized dragon fruit orchard. Dragon fruit farm in the village of Lubuk Lancang was good to effort. Where R/C obtained at 3.16 which means that each additional Rp 1 which cost will provide revenue of 3.16 with R/C was more than one,it means that the dragon fruit farming was profitable for farmers.